Correlated health instruction in the primary grades - Dojillo, Margarita S. 1924- (s.n.], 1970)
The aim of the study is to construct a plan of correlated health instruction in the primary grades. It attempts to determine the types of correlation, the problems involved in correlation, the subject matter areas in the primary grades with which health can be correlated, the particular content of the host subjects which can be correlated to health, and the health content that can be correlated with those of the host subjects. The importance of the study is in the utilization of the proposed plan for the correlation of health in other areas of instruction.